Formulation and Evaluation of Herbal Sunscreen Cream Encompassed With Tomato, Papaya, Aloe Vera, Sandalwood Natural Extracts for Essential Sun Protection Factor and UV Protection - Anusha, V; Moulika, P; Jadhav, Shivani Chandra; Seshasarvani, Nittala; Kumar, Y. Ganesh; Sushma, K (Asian Journal of Pharmaceutical Research and Development, 2025)
The Present study aims at developing herbal sunscreen cream using natural ingredients from plant sources which helps in reducing toxicity and helps in improving safety of formulation. The trend of using herbal cosmetics has been increased due to various advantages like natural antioxidant, anti-inflammatory effects, improved moisturization, natural elegance and shine, natural UV protection with good SPF etc. Herbal sunscreens are beautifying products which are made-up of natural plant extracts that protect skin with original freshness. The objective of the present research involves formulation and evaluation of herbal sunscreen using natural material from sources such as papaya, aloe vera, sandal wood, tomato, etc. The composition includes natural ingredients such as avocado oil, almond oil, carrot seed oil, raspberry oil, etc were used to formulate herbal sunscreen. All the formulated herbal sunscreen were evaluated for different evaluation tests like color, texture, pH, Spreadability, viscosity, dilution test, thermal stability, skin irritation, after feel, Washability and for sun protection factor. The results revealed that evaluation parameters of prepared herbal sunscreen were in standard limit values. It can be finally concluded that the F5 was found to be good with respect to all the evaluation parameters like Spreadability, thermal stability and the Sun protection factor (SPF) produced was 24.99 indicating good sun protections. The F5 formulation meets with all the ideal requirements of good sunscreen and it was ideal with stability based on the composition of ingredients. The research concludes that herbal sunscreens are safe to use with less or no toxicities as compared to synthetic formulations